Impact of characteristics of organ failure and infected necrosis on mortality in necrotising pancreatitis. Issue 6 (27th June 2018) - Schepers, Nicolien J; Bakker, Olaf J; Besselink, Marc G; Ahmed Ali, Usama; Bollen, Thomas L; Gooszen, Hein G; van Santvoort, Hjalmar C; Bruno, Marco J
Abstract : Objective: In patients with pancreatitis, early persisting organ failure is believed to be the most important cause of mortality. This study investigates the relation between the timing (onset and duration) of organ failure and mortality and its association with infected pancreatic necrosis in patients with necrotising pancreatitis. Design: We performed a post hoc analysis of a prospective database of 639 patients with necrotising pancreatitis from 21 hospitals. We evaluated the onset, duration and type of organ failure (ie, respiratory, cardiovascular and renal failure) and its association with mortality and infected pancreatic necrosis. Results: In total, 240 of 639 (38%) patients with necrotising pancreatitis developed organ failure. Persistent organ failure (ie, any type or combination) started in the first week in 51% of patients with 42% mortality, in 13% during the second week with 46% mortality and in 36% after the second week with 29% mortality. Mortality in patients with persistent multiple organ failure lasting <1 week, 1–2 weeks, 2–3 weeks or longer than 3 weeks was 43%, 38%, 46% and 52%, respectively (p=0.68). Mortality was higher in patients with organ failure alone than in patients with organ failure and infected pancreatic necrosis (44% vs 29%, p=0.04). However, when excluding patients with very early mortality (within 10 days of admission), patients with organ failure with or without infected pancreatic necrosis had similar mortality rates (28% vs 34%, p=0.33). Conclusion: In patients with necrotising pancreatitis, early persistent organ failure is not associated with increased mortality when compared with persistent organ failure which develops further on during the disease course. Furthermore, no association was found between the duration of organ failure and mortality.